HUBUNGAN ANTARA FAKTOR RESIKO (UMUR DAN JENIS KELAMIN) DENGAN KELAINAN JARINGAN PERIODONTAL PADA PENDERITA DIABETES MELITUS YANG BERKUNJUNG KE POLIKLINIK PENYAKIT DALAM RSUD SANJIWANI GIANYAR TAHUN 2014 - IGA Ayu Dharmawati; IGA Raiyanti (Jurnal Kesehatan Gigi (Dental Health Journal), 2015)
Dental and oral disease can become a risk factor of other disease, such as the focal infection of tonsilitis, otitis media, bacteremia, tocksemia, systemic disease like diabetes mellitus, and can also manifest with the oral cavity. Diabetes mellitus has a very close relationship with abnormality in periodontal tissue in which DM patients who has poorcontrol over oral hygiene and high sugar level is a good medium for the development of bacteria in the oral cavity. Therefore, the researcher is interested to study this with the objective of knowing the relationship between the risk factor (age and gender) and the condition of periodontal tissue of DM patients.This study used cross sectional study by analyzing secondary data of the condition of periodontal tissue of DM patients which was conducted in RSUD Gianyar in June 2014.The finding shows that there is a relationship between age and periodontal abnormality in DM patients with p value of 0.0025 (p 0.05). There is no relationship in DM patients with p value between gender and periodontal abnormality with p value of 0.193 (p 0.05).The conclusion is that there is a relationship between age and periodontal abnormality in DM patients. DM patients are recomended to visit dental clinics to consult and aget dental or oral care.